Equalizing The Legislative Functions of The Regional Representative Council And The House of Representatives Toward An Accountable Pure Bicameral System - Myaskur, Myaskur (Kadiri Islamic University, 2026)
This study aims to examines the constitutional and institutional prospects of equalizing the legislative functions of the Regional Representative Council (DPD) and the House of Representatives (DPR) as a strategic pathway toward establishing a fully accountable strong bicameral system in Indonesia. Normatively, the existence of the DPD is intended to represent regional interests within national policymaking; however, its legislative authority remains significantly limited compared to that of the DPR. This imbalance has resulted in a weak bicameral structure, undermining the principles of checks and balances and diminishing the effectiveness of regional representation. Employing a normative juridical method combined with a comparative constitutional approach, this study analyzes the existing constitutional framework, relevant statutory regulations, and practices in selected bicameral systems. The findings reveal that the current asymmetry in legislative powers constrains the DPD’s role to a merely advisory body, thereby failing to meet the standards of strong bicameralism characterized by co-equal authority in legislation, oversight, and budgetary functions. This article argues that constitutional reform potentially through a Fifth Amendment to the 1945 Constitution is necessary to recalibrate the distribution of powers between the two chambers. Strengthening the DPD’s legislative capacity would not only enhance institutional accountability but also ensure more substantive regional participation in national governance. Ultimately, the equalization of legislative functions is essential for realizing a balanced, effective, and accountable bicameral system that aligns with democratic principles and Indonesia’s pluralistic structure.